Effect of a pH-controlled co-precipitation process on rhodamine B adsorption of MnFe2O4 nanoparticles. Issue 12 (12th February 2018) - Lamdab, Umaporn; Wetchakun, Khatcharin; Kangwansupamonkon, Wiyong; Wetchakun, Natda
Abstract : The MnFe2 O4 -pH 10.5 sample exhibited high adsorption capacity towards rhodamine B (RhB) solution. The high adsorption capacity towards RhB can be attributed to the large pore size and negative surface charge of MnFe2 O4 nanoparticles. Abstract : We investigated the effect of a pH-controlled co-precipitation process on the adsorption behavior of manganese ferrite (MnFe2 O4 ) nanoparticles as well as their structural and magnetic properties. The pH of prepared MnFe2 O4 nanoparticles is typically an important factor affecting the adsorption capacity of an adsorbent. In this study, MnFe2 O4 nanoparticles were prepared using a co-precipitation method at four different pH values of 9.0, 9.5, 10.0, and 10.5. The adsorption behaviors on rhodamine B (RhB) by MnFe2 O4 nanoparticles prepared at different pH values were investigated. It was found that, via a pH-controlled process, MnFe2 O4 nanoparticles prepared at pH 10.5 showed the highest RhB removal efficiency. The results indicated that the large pore size and surface charge of MnFe2 O4 nanoparticles improved the adsorption capacities for RhB. Kinetic data were fitted to a pseudo-second order kinetic model and revealed that equilibrium was reached within 60 min. The isotherm data showed that the Langmuir maximum adsorption capacity of the MnFe2 O4 nanoparticles prepared at pH 10.5 for RhB was 9.30 mg g −1 .